Exploring the properties of cost overrun risk propagation network (CORPN) for promoting cost management - Chen, Yun; Hu, Zhigen; Liu, Quan (Journal of Civil Engineering and Management, 2019)
Construction cost overrun chronically plagues contractors. To address the issue, numerous studies have explored cost overrun risks (CORs). Nevertheless, their methods of identifying risk relationship are susceptible to experts’ experience. In addition, they fail to unearth the relationship structure information and analyze the risk propagation effect. To fill these gaps, this paper intends to propose a methodology that integrates the engineering case analysis and complex network theory, so as to obtain a stable relationship structure and reveal its inherent property. First, 52 CORs and 158 risk paths are extracted from 156 engineering cases, followed by the establishment of a cost overrun risk propagation network (CORPN). Finally, the statistical properties of CORPN are explored. The results indicate that CORPN presents the topological property of heterogeneity. A large number of risk paths can be blocked through preventing the CORs with large total degree, like delay in construction period and engineering quantity increase. Meanwhile, CORPN shows the small-world property. The efficiency of risk propagation can be reduced through preventing the CORs with high betweenness centrality, such as lack of technical skill and experience. These findings contribute to the formulation of beforehand strategies that promote the cost management.